DIGITILISATION OF THE KUTOREJO SME ECOSYSTEMINTEGRATION OF QRIS AND SMART PACKAGING AS ASTRATEGY TO IMPROVE COMPETITIVENESS: DIGITALISASI EKOSISTEM UMKM KUTOREJO INTEGRASIQRIS DAN SMART PACKAGING SEBAGAI STRATEGIPENINGKATAN DAYA SAING - Arshy Prodyanatasari; Nurul Khasanah; Nerina Ardana Shepia Putri; Niken Nadia Wati; Mukhamad Anang Ma’ruf; Muhammad Zahra Zidan Putra A; Nashrul Nur Hasanah; Shofi Mabruro (PT. ROCE WISDOM ACEH, 2026)
Digital limitations and low product innovation pose significant challenges for rural MSMEs in improving their competitiveness. This study aims to analyse the implementation and impact of an empowerment programme that integrates the QRIS digital payment system with the development of smart packaging in toast SMEs in Kutorejo Village, Mojokerto. The method used is Participatory Action Research (PAR) with a mixed-methods approach, carried out in three main stages: participatory observation, training and mentoring intervention, and comprehensive evaluation. Participants consisted of one target SME actor, 20 community members, and 15 consumers selected purposively. Data were collected through observation, in-depth interviews, questionnaires, and documentation, then analysed thematically and descriptively. The results showed that the QRIS adoption rate reached 100%, transaction efficiency increased by 80%, and sales grew by 20-30% after the implementation of smart packaging. Qualitative findings revealed an increase in digital literacy from 45% to 92% and a growth in business confidence. The discussion identified that the synergy between QRIS and smart packaging created a holistic digital ecosystem, with intensive assistance as a key factor for success. However, the sustainability of the programme faced challenges in terms of scalability and dependence on digital infrastructure. It was concluded that this integrative model was effective as a strategy to increase the competitiveness of rural MSMEs.